Analisis Faktor - Faktor yang Mempengaruhi Pengembalian Pinjaman Bmt di Kecamatan Ngaglik Tahun 2012 - Unggul Priyadi (Jurnal Aplikasi Bisnis, 2016)
This study aims to determine the profile of debtors and to analyze the changes of the variables that affect the probability of loan repayment by the customer. The data are obtained from questionnaires which distribute to four BMTs in Ngaglik namely BMT Al-Ikhwan, BMT Agawe Makmur, and BMT Partner Ummah Welfare. Logistic regression Hosmer and Lemeshow Goodness value Off Fit Test and R2 Kerke Nagel concluded that the income variable has a positive and significant effect, the variable of interest has a negative influence, the kind of work has a positive impact, and general customer District of BMTN ngaglik has a good chance against repayment of BMT Keywords: BMT, Loan, Logistic Regression, Sharia.